Design and Analysis of Blower Impeller : DOI: 10.56815/IJEMS.V3.I2.2023/1-7 (International Journal of Engineering Management Science, 2023)
The primary objective of this study is to design and analysis of a blower impeller with the usage of many engineering methods and tools. This blower impeller is an important element of various commercial and industrial applications. Its efficiency and performance effects straight to the general procedure efficiently. In optimizing the overall system’s performance, the blower impeller plays a significant role. The results of this study are used to detect the crucial areas in the impeller which need modification or demand further support. This study is successful in terms of designing and exploring a blower impeller that fulfills design demands and specifications which optimizes efficiency and performance. In general, this study reveals the value of using many engineering tools and methods in terms of analysis and design of blower impeller.
Keywords: Blower; Impeller; Casing; Design; Analysis